Clinical management of very small pigmented lesions: Improved clinical outcome through dermoscopy and reflectance confocal microscopy combination. Issue 5 (24th March 2020) - Persechino, Flavia; Franceschini, Chiara; Iorio, Alessandra; Carbone, Anna; Ferrari, Angela; Buccini, Pierluigi; Piemonte, Paolo; Eibenschutz, Laura; Sperduti, Isabella; Cota, Carlo; Frascione, Pasquale; Ardigo, Marco
Abstract: Introduction: Small‐sized pigmented lesions (SSPL) <3 mm in diameter are common pitfall in the daily dermatology practice. Dermoscopy alone is hampered by the lack of specific features inversely proportional to the diameter of the lesions and its performance is highly operator‐dependent. Reflectance confocal microscopy (RCM) has been demonstrated to be effective in the diagnosis of several difficult lesions where dermoscopy lacks to provide conclusive information. Materials and Methods: A total of 179 lesions with uncertain or equivocal clinical and dermoscopy appearance were selected. Dermoscopist has been requested to express a diagnostic suspect when possible. Equivocal lesions underwent RCM performed by expert for second‐level evaluation before surgical excision for histological diagnosis. Results have been later statistically analysed. Results: Dermoscopy was not diagnostic in large number of lesions with low concordance histology (39.1%) instead of a much high concordance when combined with RCM (93.9%). Conclusions: Small‐sized pigmented lesions were more likely to be located on the face area. Diagnosis of pigmented BCC was relatively easy on dermoscopy and also in the case of small lesions showing typical signs of BCC. LM and MM have been seen to be particularly difficult to be diagnosed using only dermoscopy. The combination of digital dermoscopy and RCM represents the correct approach of SSPL.